The members of zinc finger-homeodomain (ZF-HD) transcription factors are associated with abiotic stresses in soybean: insights from genomics and expression analysis - Hafiz Muhammad Rizwan; Jiayi He; Muhammad Nawaz; Keyu Lu; Mingfu Wang (BMC Plant Biology)
Abstract Background Zinc finger homeodomain (ZF-HD) belongs to the plant-specific transcription factor (TF) family and is widely involved in plant growth, development and stress responses. Despite their importance, a comprehensive identification and analysis of ZF-HD genes in the soybean (Glycine max) genome and their possible roles under abiotic stress remain unexplored. Results In this study, 51 ZF-HD genes were identified in the soybean genome that were unevenly distributed on 17 chromosomes. All GmZF-HD genes contained a conserved ZF-HD_dimer domain and had diverse physicochemical features. Furthermore, the GmZF-HD gene structures exhibited 3 to 10 conserved motifs, and most of them showed intronless gene structures. Phylogenetic analysis categorized them into eight major groups with the highest closeness to dicots including Brassica rapa and Malus domestica. The cis-element analysis recognized plant growth and development (10%), phytohormones (31%) and stress-responsive (59%) elements. Synteny analysis identified 73 segmental and 1 tandem duplicated genes that underwent purifying selection. The collinearity analysis revealed that GmZF-HD genes showed higher homology with dicot species, indicating common ancestors with close evolutionary relationships. A total of 94 gma-miRNAs from 41 diverse miRNA families were identified, targeting 40 GmZF-HD genes, with GmZF-HD6 being most targeted by 7 miRNAs, and gma-miR4993 emerging as the dominant miRNA family. Different TFs including ERF, LBD, BBR-BPC and MYB, etc., were predicted in all 51 GmZF-HD genes upstream regions and visualized in the network. Expression profiling through RNA-Seq showed diverse expressions of GmZF-HD genes in different tissues including seeds, roots, shoots and leaves under diverse conditions. Further, the qRT-PCR analysis demonstrated that all tested GmZF-HD genes were significantly induced in soybean leaves, mainly the GmZF-HD5/6/13/39 and GmZF-HD45 genes were significantly upregulated (2.5 to 8.8 folds) under the tested stress treatments compared to control, highlighting their potential roles in response to stresses in soybean. Conclusion Overall, this study reveals comprehensive insights into the ZF-HD genes in soybeans and provides a valuable contribution towards functional studies for soybean improvement under stress conditions.